Phosphate Adsorption Capacity and Organic Matter Effect on Dynamics of P Availability in Upland Ultisol and Lowland Inceptisol - Marsi, .; Sabaruddin, . (JOURNAL OF TROPICAL SOILS, 2011)
Ultisols and Inceptisols were used to investigate the adsorption-desorption capacity of P and the effect of organic matter on the dynamics of P availability in tropical acid soils. The experiment consisted of two sub-experiments. Sub-experiment I was to study the adsorption-desorption capacity of Ultisols, Fresh-water lowland Inceptisols, and tidal-swamp Inceptisols. Therefore, surface soils (0 to 30 cm) of each tested soil were treated with 0, 10, 20, 30, 40, 60, 80, 100, 120, 140, 170, and 200 mg P kg-1 of soil. Sub-experiment II was to study the effects of organic matterapplication (0, 5, 10, and 15 Mg ha-1) on the dynamics of available P following 60d incubation under room temperature.P fertilizer application significantly affected water soluble-P (WSP) (p<0.01) and soil available P-Bray and Kurtz No. 1 (BKP) (p<0.01) in the three tested soils. The different response of both WSP and BKP confirmed that the soils tested in the current experiment had different soil P buffering capacity in the order of Tidal-lowlandInceptisol>Upland Ultisol>fresh-water Lowland Inceptisol. OM application increased the BKP in all tested soils as compared to the control. Differences in pattern of soil available P dynamics over time were detected between upland soil and two lowland soils used in the current experiment.Keywords: Adsorption-desorption, Inceptisols, organic matter, Ultisols